1983
DOI: 10.1136/jmg.20.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Consanguineous matings in the Egyptian population.

Abstract: SUMMARY A total of 26 554 Egyptians was ascertained to study the incidence of consanguineous marriages. They were of different ages, different socioeconomic standards, and from different areas. There were 7646 from urban areas, 11 280 from suburban areas, and 7628 from rural areas.The incidence of consanguineous matings in the general population was found to be 28-96% with an average inbreeding coefficient of 0-010, which could be considered high. The highest incidence was that in the rural areas. First cousin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 3 publications
10
83
0
1
Order By: Relevance
“…A study performed within Sana'a City, Yemen revealed a incidence of consanguinity of 44.7%, with first-cousin marriages comprising 71.6%, and an average coefficient of inbreeding (the probability of an individual having two alleles identical by descent at a given locus) of 0.02442, 59 almost double that of the Egyptian population (0.01) 60 and four times that of the Turkish population (0.0064532). 61 Similar studies conducted in Qatar indicate a rate of consanguinity of 54.0% (first cousin marriages accounting for 34.8%) and a coefficient of inbreeding of 0.02706, 62 whereas comparable consanguinity values were observed in UAE (50.5%) 63 and Oman (35.9%).…”
Section: Regional Autosomal Str Analysismentioning
confidence: 99%
“…A study performed within Sana'a City, Yemen revealed a incidence of consanguinity of 44.7%, with first-cousin marriages comprising 71.6%, and an average coefficient of inbreeding (the probability of an individual having two alleles identical by descent at a given locus) of 0.02442, 59 almost double that of the Egyptian population (0.01) 60 and four times that of the Turkish population (0.0064532). 61 Similar studies conducted in Qatar indicate a rate of consanguinity of 54.0% (first cousin marriages accounting for 34.8%) and a coefficient of inbreeding of 0.02706, 62 whereas comparable consanguinity values were observed in UAE (50.5%) 63 and Oman (35.9%).…”
Section: Regional Autosomal Str Analysismentioning
confidence: 99%
“…[33][34][35][36][37][38] They too emphasize the higher rates of consanguineous marriage in their communities and the finding of hereditary nonpolyposis CRC in a proportion of patients. 12,[38][39][40] The most complete published data is from the Kingdom of Jordan and confirms the higher risk for rectal cancer in their population as compared to SEER or Israeli data. 41 A Middle East Consortium monograph, comparing malignant diseases in 5 Middle Eastern populations, 1996-2002, is now being published by the National Cancer Institute (USA).…”
Section: Discussionmentioning
confidence: 74%
“…The mean inbreeding coefficient of the screened population in South Sinai was 0.0184. In previous studies the average inbreeding coefficient in the Egyptian population was found to be 0.010-0.0117 (Hafez et al, 1983;Mohamed, 1995). These figures are considered high compared with most Western societies, where the average inbreeding coefficient is usually less than 0.001 (Bittles, 2011).…”
Section: Resultsmentioning
confidence: 92%
“…Studies on the frequency of parental consanguinity in the Egyptian population have given figures ranging from 20.9 to 32.8% (Stevenson et al, 1966;Hafez et al, 1983;Mohamed, 1995;Mokhtar & Abdel-Fattah, 2001), except for Nubia in the south where consanguinity raes as high as 60-80% have been reported (Hussien, 1971;Badr, 1972). Consanguinity rates were found to be higher in rural than in urban settings (Hafez et al, 1983). The most common consanguineous marriages in Egypt occur between first cousins (50%), followed by first cousins once removed (15%), second cousins (15%) and other more distant relations (Hafez et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation